Applications of Knowledge Graphs in the Portuguese Language: A Systematic Literature Review - Lima, Maurício; Oliveira, Vinícius; Oliveira, Sávio; Dias, Elisângela (Anais do Congresso Latino-Americano de Software Livre e Tecnologias Abertas (Latinoware); 2025: Anais do XXII Congresso Latino-Americano de Software Livre e Tecnologias AbertasDO - 10.5753/latinoware.2025.16271, 2025)
This paper presents a Systematic Literature Review on applications of knowledge graphs in the Portuguese language. PRISMA 2020 and Parsifal were used for planning, execution, and documentation. Searches in databases such as ACM Digital Library, EI Compendex, IEEE, Web of Science, SciELO, ScienceDirect, Scopus, Sol SBC, and Springer Link retrieved 513 records; after deduplication, screening, and full-text eligibility assessment, 12 primary studies were included. For each study, we extracted the domain and objective, types of input data, graph size (when reported), construction and integration techniques, tools/frameworks, update and maintenance strategies, use of inference, evaluation metrics, and quantitative results. The findings reveal recurring benefits of publishing in open standards (RDF/OWL/SPARQL), practical utility in downstream tasks, and the feasibility of construction through extraction/clustering, rules/transformations, and, more recently, LLM-assisted workflows. Four usage archetypes were identified: broad-scope lexical resources, domain-oriented KGs, knowledge modules coupled with pipelines, and reference/evaluation resources.